Statistical Light on Profits, as Analyzed in Recent Literature - Epstein, Ralph C. (Quarterly Journal of Economics, 1930)
General character of the two studies, 320.—Crum's analysis of earning power: the "profit ratio, " 322; the "earnings ratio, " 326.—The return Upon capital invested, 330.—The proportion of profitable operations, 333.—Sloan's analysis of earnings, 334.—Frequency distribution of earnings in 1927 and 1917, 336.—The range of earnings, 339.—Relation between earnings and "especialty products, " 340.—More light needed, 342.